ANEMIA OF CHRONIC DISEASE - Bogun, L. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
The lecture deals with one of the commonest forms of anemia which develops secondary to systemic illnesses as an inflammatory response. Main causes, pathogenesis, clinical manifestation of anemia of chronic disease and basic approaches to its diagnostics and treatment are described.